Gewalt und Ästhetik : zur Gewalt und ihrer Darstellung in der griechischen Klassik - Seidensticker, Bernd; Vöhler, Martin (De Gruyter, 2006)
Violence and the forms of its representation are a long neglected central element of Classical Greece. After reviewing the history of the 5th century BC with its intensive experience of violence, the studies in this volume examine the tension between violence and aesthetics in the fields of myth, cult, and literature with particular reference to tragedy and visual art.